Effect of Root System Distribution on Slope Stability - LIU Jun (Renmin Zhujiang)
The effects of plant root system on the stability of slope depend on its complex growthand morphological distribution. Taking vetiver root system as the research object, this paperderives a formula for calculating the safety factor of the slope considering the distributionangle of plant root system theoretically, and verifies its reliability by triaxial test. Theresults show that: ① Compared with the plain soil, the shear strength of root-reinforced soilincreases correspondingly, and the increase is more obvious when the inclination of the rootsystem is 156°; ② For root system with different inclination, the values of c and φ of root-reinforced soil also increase compared with the plain soil, but the increase of cohesive force ismore obvious than that of internal friction angle, with better increase effect under 156°inclination.